Comparative Analysis of Financial Performance: A Study of Machhapuchchhre Bank and Sanima Bank - Khatiwada, Atmaram (Journal of Durgalaxmi, 2025)
Financial indicators that are critical with regard to decision making, monitoring of performance, and strategic planning in commercial banks include profitability, asset quality, and capital adequacy, especially in the financial systems that are developing, such as Nepal. Although they are crucial, not much research has been done to determine the combined effect of these indicators on the decision of managers, risk management, and investor confidence. This research is a descriptive-correlational quantitative research, which is utilized to examine the financial performance of Machhapuchchhre Bank Limited (MBL) and Sanima Bank Limited (SBL) using secondary data based on annual reports, audited statements, and publications of Nepal Rastra Bank. The data was manipulated in SPSS using descriptive statistics, correlation, and regression analysis. Findings indicate that profitability and capital adequacy positively and significantly impact strategic decision-making and investor confidence, but increased non-performing loans negatively impact the profitability and general quality of decisions. The results propose the idea that an appropriate level of liquidity, an increased capital level, and a low level of credit risk contribute to sustainable growth and financial stability. The research also has useful implications to enhance decision-making and policymaking by managers in the commercial banking industry in Nepal.